The role of non-verbal cues in image making on the basis of selected press advertisements showing elderly women - Kowalewska, Kinga (Scripta Neophilologica Posnaniensia, 2019)
In Europe, the population of people over 60 years old has increased dramatically in the last few decades. Due to the demographic changes, in Poland, the world of marketing seems to discover the purchasing power of the elderly. Seniors become not only the receivers but also the senders of advertising messages. In order to sell a product, ad makers present people who are supposed to be liked, trusted, identified with and finally followed. In a press advertisement, to which an average consumer devotes 1.5 seconds, the picture is of top priority. The present research aims at analyzing the image of elderly women in press advertisements on the basis of their physical appearance, the context of the depicted situation, their clothes, facial expressions, eye-contact, and other visible traits. The survey study was conducted among young people to see the difference in their perception of elderly women in the pictures illustrating press advertisements for different products. The research results show how the positive image of the elderly in advertising can be created.